Sail away - Imrie, Celia, 1952- (Bloomsbury USA, an imprint of Bloomsbury Publishing Plc, 2018)
The phone hasn't rung for months. Suzy Marshall is discovering that work can be sluggish for an actress over sixty--even for the star of a wildly popular 1980s TV series. So when her agent offers her the plum role of Lady Bracknell in The Importance of Being Earnest in Zurich, it seems like a godsend. Until, that is, the play is abruptly cancelled under suspicious circumstances and Suzy is forced to take a job on a cruise ship to get home. Meanwhile Amanda Herbert finds herself homeless in rainy Clapham. The purchase of her new apartment has fallen through, and her children are absorbed in their own dramas. Then she spots an advertisement for an Atlantic cruise and realizes that a few weeks onboard would tide her over and save her money until her housing situation is resolved. As the two women set sail on a new adventure, neither can possibly predict the questionable characters and strange dealings they will encounter, nor the unexpected rewards they will reap.